Interaction of noradrenergic and cholinergic agonists with ligands increasing K-conductance of guinea pig hippocampal neurons, in vitro - Bijak, Maria; Misgeld, Ulrich; Müller, Wolfgang (European journal of neuroscience, 1991)
Single electrode current clamp and voltage clamp recordings were employed to study the effects of noradrenergic agonists and a cholinergic agonist (carbachol, Cch) on the resting membrane potential of CA3 neurons in guinea pig hippocampal slices. Stimulation of muscarinic and β-adrenergic receptors depolarized, and stimulation of α1-adrenergic receptor hyperpolarized, CA3 neurons but the membrane potential changes were small. Hyperpolarizations or outward currents induced by baclofen, adenosine or serotonin (5-HT) were strongly potentiated by α-noradrenergic agonists and suppressed by Cch at concentrations ten times lower than those having any direct effects on membrane potential. Both the enhancement of the baclofen-induced hyperpolarization by phenylephrine and its suppression by Cch were pronounced at low concentrations of baclofen, but diminished at higher concentrations. The modulatory effects persisted after blockade of sodium spikes by tetrodotoxin and after blockade of fast inhibitory and excitatory synaptic transmission by picrotoxin and 6-cyano-7-nitroquinoxaline-2,3-dione. Our data suggest that, through the postsynaptic interaction with ligands activating potassium conductance, noradrenergic and muscarinic receptor stimulation can exert a stronger inhibitory and excitatory effect on CA3 pyramidal neurons at their resting membrane potential than would be expected from the changes in membrane potential induced by these neuromodulators on their own.
Elektronische Reproduktion der Druck-Ausgabe
Online: 07 April 2006
Gesehen am 26.04.2021